Detection of hydrogen sulfide above the clouds in Uranus's atmosphere. (May 2018) - Irwin, Patrick; Toledo, Daniel; Garland, Ryan; Teanby, Nicholas; Fletcher, Leigh; Orton, Glenn; Bézard, Bruno
Abstract Visible-to-near-infrared observations indicate that the cloud top of the main cloud deck on Uranus lies at a pressure level of between 1.2 bar and 3 bar. However, its composition has never been unambiguously identified, although it is widely assumed to be composed primarily of either ammonia or hydrogen sulfide (H2 S) ice. Here, we present evidence of a clear detection of gaseous H2 S above this cloud deck in the wavelength region 1.57–1.59 μm with a mole fraction of 0.4–0.8 ppm at the cloud top. Its detection constrains the deep bulk sulfur/nitrogen abundance to exceed unity (>4.4–5.0 times the solar value) in Uranus's bulk atmosphere, and places a lower limit on the mole fraction of H2 S below the observed cloud of (1.0-2.5)× 10^-5 ( 1.0 - 2.5 ) × 1 0 - 5 . The detection of gaseous H2 S at these pressure levels adds to the weight of evidence that the principal constituent of 1.2–3-bar cloud is likely to be H2 S ice. Ground-based near-infrared spectra of Uranus detected hydrogen sulfide (H2 S) above the main cloud deck (at a pressure of 1.2–3 bar), suggesting that the bulk sulfur/nitrogen ratio in Uranus's atmosphere exceeds unity and that the clouds are dominated by H2 S ice.